MRI of the Female and Male Pelvis - Manfredi, Riccardo; Pozzi Mucelli, Roberto (Springer International Publishing : Imprint: Springer, 2015)
Based on the experience of two Italian referral centers, the book depicts the characteristic findings obtained when using MR imaging to study the male and female pelvis including the obstetric applications. Each chapter provides a comprehensive account of the use of the imaging technique of examination, including the most recent advances in MR imaging, the anatomy and MR possibilities in the identification, characterization and staging of the different pelvic diseases highlighting its diagnostic possibilities. The advances in fetal MRI, representing the cutting edge of pelvic MR imaging, will also be depicted. The text is complemented by numerous illustrations, as well as clinical cases that make this a very practice-oriented work, presenting the role of diagnostic imaging in every-day clinical activity. The volume will prove an invaluable guide for both residents and professionals with core interest in gynecology, obstetrics and urology.